Testing and Dissemination of Improve Varieties and Agronomic Practices Using the 'Mother-Baby' Approach - International Institute of Tropical Agriculture; Savannah Agricultural Research Institute (International Food Policy Research Institute, 2015)
This study explores raising and sustaining productivity in cereal-legume cropping systems in northern Ghana. Project title: AfricaRISING - Sustainable Intensification of Cereal-Based Farming Systems in the Guinea-Sudan-Savanna of Ghana and Mali. Project abstract: In 2013, four mother-baby trials started to test and demonstrate crop variety and combinations of variety and agronomic options will continue for the second year. A split-plot design replicated in 4-6 communities per region will be used in the trials with 30 babies per community for each mother trial. Project website: https://africa-rising.net